(3bQi GdVja aj hUa CjGe GdUjas - (3CHj YHO Gddg TQa GdOjf GdMSjf Hf QjGfs ((3Ydj Hf UGdM Hf bWH GdOjf Hf Jhcd GdeQfOj s)
(3ChdgG (B:s
(3GeG HYO MeO Gddg Ydi eG Cdge ef MeOg, hTcQg Ydi MQ GdReGf hHQOg Pgd ajg GdacQ hMGQ, s
(3BNQgG (B:s
(3adh Cf Cgd GdfGQ aj eKd efRdj dHGOh LejYkG eG JNda EfSGf jJdhgG QSGdI GdRdRdI aj GdMGPKI s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B101 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9257) s
Keywords: (3GdCOHs